Study of early screening of potato (Solanum tuberosum L.) as a result of drought stress (in vitro) - . Charloq; Ernitha Panjaitan; Bilter A. Sirait (Syiah Kuala University, 2012)
Preliminary studies in Screening of Potato (Solanum tuberosum L.) as a result of drought stress (in vitro). This study aim was to determine the limits of potato (Solanum tuberosum L.) to drought stress conditions in vitro using PEG. This research was conducted at the Tissue Culture Laboratory Unit / Laboratorium Kultur Jaringan UPT/Balai Benih Induk Hortikultura Dinas Pertanian Propinsi Sumatera Utara, Jl. Karya Jasa No. 6 Gedung Johor Medan in March 2012 to June 2012. The Completely Randomized Design (non factorial) was used with PEG concentrations of five levels, namely: P1 = 10%, P2 = 20%, P3= 30%, P4 = 40% and P5 = 50% with 5 replications. The results showed that increasing the concentration of PEG will reduce the percentage of plantlets survival, reduce plant height, number of roots and number of nodes. Treatment of 50% PEG resulted in the death of potato cuttings due to drought stress.